Analisis Minat Berwirausaha Mahasiswa Jurusan Adminstrasi Bisnis Politeknik Negeri Sriwijaya - Mariskha Z (Politeknik Negeri Sriwijaya, 2020)
This research was conducted to determine the effect of entrepreneurial achievement subject to student interest in entrepreneurship Department of Business Administration Politeknik Negeri Sriwijaya. The population in this study were 133 people, and the sample in this study was 40 people. The statistical analysis used was a simple linear regression analysis. Based on the analysis of the obtained effect of learning achievement (x) 8,2% of the interest in entrepreneurship (y), while the remaining 91,8% is influenced by other factors. Althogh significant influence but is still very small, it can be caused by values, entrepreneurial behavior, characteristics, and entrepreneurial character not owned by business administration students Politeknik Negeri Sriwijaya.